2001
DOI: 10.1038/sj.bmt.1703087
|View full text |Cite
|
Sign up to set email alerts
|

Acute autoimmune hemolytic anemia following unrelated cord blood transplantation as an early manifestation of chronic graft-versus-host disease

Abstract: Summary:A 16-month-old girl diagnosed with osteopetrosis underwent an unrelated, partially matched (with major mismatch at A locus) cord blood stem cell transplant. Twelve months later she developed severe acute autoimmune hemolytic anemia (AIHA). Immunophenotype analysis of lymphocyte subsets 8 months post transplant showed a low number of T lymphocytes, with normal subsets, and with NK cells and B lymphocytes within normal ranges. When the hemolytic anemia developed, the lymphocytes subsets changed and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 9 publications
0
18
0
2
Order By: Relevance
“…[25][26][27][28] In fact, AIHA can even be a presenting sign of cGVHD. 8,29 The mechanism by which allogeneic cellular activation leads to a humoral autoimmune disorder is unclear. It has also been suggested that CyA could impair development of immune tolerance in the post-transplant period and thus induce the development of autoimmune reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28] In fact, AIHA can even be a presenting sign of cGVHD. 8,29 The mechanism by which allogeneic cellular activation leads to a humoral autoimmune disorder is unclear. It has also been suggested that CyA could impair development of immune tolerance in the post-transplant period and thus induce the development of autoimmune reactions.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, the incidence and risk factors for the development of AIHA, as well as its prognosis and response to treatment are still not well defined. In fact, our current knowledge of AIHA is based on single case reports [6][7][8][9] and small series in adults 4,10 and children. 5 The aim of the study was to analyze the characteristics of patients and transplants, as well as outcome, in a series of patients who developed AIHA after allogeneic HSCT at a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…A case report of AIHA after CBT for osteopetrosis also showed a low number of T lymphocytes by immunophenotype analysis. 12 Indeed, unbalanced B and T lymphopoiesis has been proposed to favor the development of the antired blood cell antibodies causing AIHA. 9 In addition, in vivo T-cell depletion by antihuman thymocyte globulin in our patient might have played a role in the development of Evans syndrome.…”
Section: Evans Syndrome After Unrelated Cord Blood Transplantation Fomentioning
confidence: 99%
“…Additional reports have included several cases following cord blood transplants, with resultant AIHA and Evans syndrome. 25,26 There have been reports of successful therapy of AIHA following hematopoietic stem cell transplantation with rituximab.…”
Section: Association Of Immune Hemolysis With Allogeneic Hematopoietimentioning
confidence: 99%